Analysis of volatile compounds and flavor fingerprint in hairtail (Trichiurus lepturus) during air-drying using headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) - Liao, Yueqin; Ding, Yixuan; Wu, Yingru; Du, Qi; Xia, Jiangyue; Jia, Junqi; Lin, Huimin; Benjakul, Soottawat; Zhang, Bin; Hu, Yi (Frontiers in Nutrition, 2023)
To investigate the generation of aroma in hairtails during air-drying, changes in volatile compounds during processing were analyzed using headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS). Physicochemical indices such as moisture content and thiobarbituric acid reactive substances (TBARS) were also detected. Flavor fingerprints were built to distinguish the samples of fresh hairtails (0 d) from air-dried hairtails (2 and 4 d). A total of 75 volatile organic compounds (VOCs) were identified in hairtails, in which alcohols, aldehydes, ketones, and esters were the principal contributors to the formation of the overall flavor of hairtails during air-drying. Seven flavor compounds (ethanol, 3-methyl-1-butanol, 1-pentanol, hexanal, octanal, benzaldehyde, and 3-methylbutanac), two flavor compounds (acetoin and dimethyl sulfide), and eight flavor compounds (1-hexanol, 1-octen-3-ol, nonanal, heptanal, 2-heptanone, ethyl acetate, trimethylamine, and ammonia) were identified in 0, 2, and 4 air-dried hairtails as biomarkers, respectively. The results showed that HS-GC-IMS could rapidly and comprehensively detect VOCs in different air-dried hairtails.